Advanced audio coding with efficient psychoacoustic modeling - Sudeendra Maddur Gundurao. (2009)
Data compression technique is an essential task for audio systems, which not only handles enormous amounts of data, but also requires the high quality resolution. One of these audio coding techniques, Moving Pictures Experts Group (MPEG) is powerful audio compression standardization. It can significantly reduce the requirements of transmission bandwidth and data storage, but with low distortion. This dissertation presents a new low complexity design of Psycho-Acoustic Model-2 (PAM), which is the key technology for a low power MPEG-2/4 Advance Audio Coding (ACC) encoding. The real-time constraint of MPEG ACC leads to a heavy computational bottleneck on today’s portable devices. To overcome this problem, design analysis and optimization of PAM are addressed. At algorithmic level, a new Modified-Discrete-Cosine-Transform-based (MDCT-based) PAM is designed and implemented concerning major reduction in complexity and also improving quality of the coded audio. In addition, the calculation of spreading function was replaced with look-up tables. The computational complexity of the proposed single transform New MDCT-based PAM (Model-C) could be reduced by more than 85% when compared to the classical FFT-based PAM (Model-A) and by around 40%when compared to the dual transform MDCT-based PAM (Model-B) suggested in [33]. The proposed new design makes it possible to implement the computationally intensive classical MPEG-2/4 AAC stereo encoder in real-time by sufficiently reducing its complexity.